X-linked lymphoproliferative disease type 1: a clinical and genetic update - Li, Jiaxun; Lv, Luyu; Wei, Qingqing; Pang, Wenpeng; He, Chunjuan; Wu, Hao; Guo, Liping (Frontiers in Immunology, 2025)
X-linked lymphoproliferative disease (XLP), also known as Duncan’s disease, is a primary immunodeficiency disorder linked to the X chromosome. In 1998, SH2D1A, which encodes the signaling lymphocyte activation molecule (SLAM)-associated protein (SAP), was identified as the first pathogenic gene associated with XLP. To date, more than 100 mutation sites in this gene have been documented. The disease is associated with infection with Epstein-Barr virus (EBV) and characterized by hemophagocytic lymphohistiocytosis (HLH), hypogammaglobulinemia, and lymphomas. Pathogenesis is intricately associated with cell type-specific SAP-SLAM signaling pathways. Particularly, the immune cell defects involve impaired T cell-B cell interactions, reduced cytotoxicity of Natural Killer (NK) cells, and abnormal development of Natural Killer T (NKT) cells. These factors collectively increase susceptibility to EBV and drive clinical manifestations in XLP type 1 (XLP1) patients. Although establishing a definitive correlation between specific genotypes and clinical phenotypes remains challenging, emerging evidence suggests a potential association. This underscores the critical need for further large-scale studies to elucidate this relationship. Given the current understanding of the pathophysiological mechanisms associated with XLP1, specific treatments to normalize SAP expression and restore immune tolerance in XLP1 patients play an important role. In addition to the necessity for long-term studies to verify the efficacy and safety of hematopoietic stem cell transplantation (HSCT), gene therapies currently under development, along with other emerging treatments, exhibit substantial promise for future clinical applications.